Typhoid Fever, Water Quality, and Human Capital Formation. (25th February 2016) - Beach, Brian; Ferrie, Joseph; Saavedra, Martin; Troesken, Werner
Abstract : New water purification technologies led to large mortality declines by helping eliminate typhoid fever and other waterborne diseases. We examine how this affected human capital formation using early-life typhoid fatality rates to proxy for water quality. We merge city-level data to individuals linked between the 1900 and 1940 Censuses. Eliminating early-life exposure to typhoid fever increased later-life earnings by one percent and educational attainment by one month. Instrumenting for typhoid fever using typhoid rates from cities that lie upstream produces results nine times larger. The increase in earnings from eliminating typhoid fever more than offset the cost of elimination.